TANTANGAN BODY DISSATISFACTION DALAM MEMBENTUK KEPERCAYAAN DIRI PADA REMAJA PEREMPUAN - Siti Mufarochah; Nur Irmayanti (Jurnal Gesi, 2023)
Body dissatisfaction can be defined as an individual perspective in assessing their body image or body size based on the experiences in the surrounding environment caused by negative thoughts. It could be a factor in an individual feel confident in solving the problems that exist in the surrounding environment. The purposose of this study was to investigate the relationship between body dissatifaction with self-konfidence at the end of the juvenile female. This study is a quantitative correlation with the number of 55 subjects taken by quota sampling. The results of the study showed that there is a significant relationship between body dissatisfaction and self-confidence in adolescent girls Kata kunci : body dissatisfaction, self-confidence, end adolescent girls